Detection of pathogenic, intermediate and saprophytic leptospira isolates from rodents in selected National Park and Urban Sites of Sarawak - Nuraqeelah, Mohammad Shamhar (Universiti Malaysia Sarawak (UNIMAS), 2015)
Leptospirosis is a global zoonotic disease caused by pathogenic Leptospira that greatly affect both human and animals. The infection has become an urban public health concerns due the increase number of leptospirosis cases reported. Rats are known to be the major reservoir of Leptospira. Due to limited information regarding leptospirosis in Sarawak, this study aims to isolate and detect Leptospira circulating among urban rat populations in Sarawak. In this study, rats were captured using cage trap in selected urban sites namely Kuching, Kota Samarahan, and Lundu. Kidney and liver tissue samples were removed and cultured in modified Ellinghausen McCullough Johnson Harris (EMJH) media. Cultures were analysed using polymerase chain reaction (PCR) for the detection of pathogenic, saprophytic, and intermediate Leptospira. This study found that there are 44% (33 out of 75) captured rats from 6 different species were detected with Leptospira. 21.21% (5 out of 33) captured rats were carrying pathogenic Leptospira whereas 84.85% (28 out of 33) captured rats were carrying saprophytic Leptospira. This study has shown that rats have high potential to be carriers of Leptospira. This study also indicates that PCR is a well recommended molecular tool with specificity and sensitivity for Leptospira detection in chronic carriers. The finding has proven the occurrence of pathogenic Leptospira in urban sites of Sarawak thus it helps to provide knowledge regarding the infections level of pathogenic Leptospira circulating among rats in the urban sites of Sarawak. Thus, improvement on basic sanitation facilities is required in the urban sites of Sarawak to control the prevalence of leptospirosis.